2016
DOI: 10.1111/tri.12816
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of intracellular adenosine triphosphate in CD4+T cells to predict the occurrence of cytomegalovirus disease in kidney transplant recipients

Abstract: SUMMARYThe measurement of intracellular concentrations of adenosine triphosphate (iATP) in phytohemagglutinin-stimulated CD4 + T cells constitutes a surrogate marker for post-transplant cell-mediated immunity (CMI). This assay has shown suboptimal accuracy for predicting infection after kidney transplantation (KT). We hypothesize that its predictive capacity depends on the specific contribution of the CMI to host-pathogen interactions. We assessed iATP levels in 100 KT recipients at baseline and months 1, 3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…An additional eight studies meeting inclusion criteria were identified from the manual review of bibliographies of published SLRs. Ultimately, 86 5,6,14‐97 citations representing 81 unique studies 5,6,14‐92 including 69 803 participants met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…An additional eight studies meeting inclusion criteria were identified from the manual review of bibliographies of published SLRs. Ultimately, 86 5,6,14‐97 citations representing 81 unique studies 5,6,14‐92 including 69 803 participants met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In 248 liver recipients, low iATP was associated with invasive fungal infection, but not bacterial infection [64]. In 100 kidney recipients, lower iATP was associated with CMV disease, but not bacterial infections [65]. Metaanalyses of iATP studies found discordant results [66][67][68].…”
Section: Immune Function Assaysmentioning
confidence: 99%
“…The principle of the test is measuring intracellular adenosine triphosphate (ATP) production in CD4 + -cells upon whole blood stimulation with phytohemagglutinin (PHA) [15]. Although the technique is promising, many of the studies conducted with ImmuKnow® have limitations including retrospective design, small number of recipients, single measurement and/or low follow-up time, and results so far are conflicting [1214, 1623]. One promising randomized controlled study by Ravaioli et al found that immunosuppression dosed according to results of serial testing with ImmuKnow® increased 1-year patient survival and lowered the incidence of infections in liver transplant patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…The use of functional assays to determine immune function has gained attention as a possible tool to improve dosage of immunosuppression in SOT recipients [1023]. Previously, functional assays have been expensive and required high level of technical skills and hands-on time in the laboratory, limiting the utility of this approach.…”
Section: Introductionmentioning
confidence: 99%